Conspicuity and bicycle crashes: preliminary findings of the Taupo Bicycle Study. Issue 1 (1st February 2008) - Thornley, S J; Woodward, A; Langley, J D; Ameratunga, S N; Rodgers, A
Abstract : Objective: To describe the methods, characteristics of participants, and report on the preliminary findings of a longitudinal study of cyclists. Design: Web-based survey to establish a cohort of cyclists. Setting: Participants in the largest mass-participation bicycle event in New Zealand, the Wattyl Lake Taupo Cycle Challenge. Participants: 2469 riders who had enrolled online in the 2006 Wattyl Lake Taupo Cycle Challenge. Main outcome measures: Self-reported crashes in preceding 12 months. Results: Of 5653 eligible riders, 2469 (44%) completed the study questionnaire. Mean age was 44 years, 73% were male, and the average number of kilometers cycled per week in the preceding 12 months was 130. The annual incidence of crashes leading to injury that disrupted usual daily activities for at least 24 h was 0.5 per cyclist/year. About one-third of these crashes resulted in presentation to a health professional. The mean number of days absent from work attributable to bicycle crashes was 0.39 per cyclist/year. After adjustment for potential confounders and exposure (kilometers cycled per year), the rate of days off work from bicycle crash injury was substantially lower among riders who reported always wearing fluorescent colors (multivariate incidence rate ratio 0.23, 95% CI 0.09 to 0.59). Conclusions: Low cyclist conspicuity may increase the risk of crash-related injury and subsequent time off work. Increased use of high-visibility clothing is a simple intervention that may have a large impact on the safety of cycling.